Development of Microsoft Sway-Based Learning Media Materials for Class VII Physical Fitness Activities - Achmad Syakur Fahri; Sulaiman Sulaiman; Bambang Priyono (JUARA : Jurnal Olahraga, 2022)
TThis study aimed to produce learning media products based on Microsoft sway that were tested for feasibility and effectiveness to improve student learning outcomes for class VII physical fitness activity materials. This study uses the development method with 300 samples of feasibility tests and 250 samples of effectiveness tests, consisting of 11 schools located in six provinces on the island of Java. Product development procedures, namely, 1) Conduct a needs analysis by conducting interviews and questionnaire surveys with 3 PJOK teachers and 672 students from 3 schools in the city of Bandung. 2) designing learning media in the form of material to be presented, 3) developing with validation of material experts and media experts as well as small group trials to find out deficiencies and revise the initial draft, 4) implement media to students by conducting a feasibility test on 300 students who are consisting of 11 different schools in six provinces on the island of Java and testing the effectiveness of the product to 250 in the provinces of Central Java and West Java, 5) evaluation of the results of the feasibility test and effectiveness test to produce a product in the form of learning media based on Microsoft sway material for physical fitness activities class VII. This research produces learning media products that are easily accessible, practical and simple. The results of the feasibility test of material experts with a percentage of 95.62% in a very decent category, media experts with a rate of 94.15% in a very decent variety, then first user teacher with a percentage of 92.08% in a very feasible category and large group trials with a rate 76.95% with proper type. The effectiveness test results the results in an increase in student learning outcomes using media that have been developed.